2022
DOI: 10.3389/fendo.2022.1029475
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bone health through physical exercise: Mechanisms and types

Abstract: Osteoporosis, characterized by bone mineral density reduction, bone mass loss, increased bone fragility, and propensity to fractures, is a common disease in older individuals and one of the most serious health problems worldwide. The imbalance between osteoblasts and osteoclasts results in the predominance of bone resorption and decreased bone formation. In recent years, it has been found that regular and proper exercise not only helps prevent the occurrence of osteoporosis but also adds benefits to osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…Similar to how mechanical stress on bones, like that brought about by exercise, increases osteocalcin production [ 19 , 20 ], the rise in osteocalcin levels seen in both groups is consistent with this theory. It is possible that the slightly higher increase in the HIRT group was caused by the heavy mechanical load that resistance training puts on the bones, which may lead to a stronger osteogenic response.…”
Section: Discussionsupporting
confidence: 75%
“…Similar to how mechanical stress on bones, like that brought about by exercise, increases osteocalcin production [ 19 , 20 ], the rise in osteocalcin levels seen in both groups is consistent with this theory. It is possible that the slightly higher increase in the HIRT group was caused by the heavy mechanical load that resistance training puts on the bones, which may lead to a stronger osteogenic response.…”
Section: Discussionsupporting
confidence: 75%
“…Long-term appropriate forms of exercise and appropriate exercise intensity can promote the balance between bone formation and bone resorption, increase bone trabecular alignment and density, accelerate bone mineralization, enhance bone mass, and improve bone metabolism by regulating the signaling molecules secreted by osteoblasts and osteoclasts ( Fonseca et al, 2014 ; Mages et al, 2021 ; Benedetti et al, 2018 ). Several studies have found that exercise can affect the levels of MOTS-c and, similarly, that it regulates osteogenic differentiation and promotes bone formation ( Benedetti et al, 2018 ; Guo et al, 2020 ; Chang et al, 2022 ; Barry and Kohrt, 2008 ). However, the exact signal transduction mechanism by which exercise improves bone health through MOTS-c remains unknown and needs to be further investigated.…”
Section: Potential Pathways Of Exercise To Promote Bone Metabolism Th...mentioning
confidence: 99%
“…Once a patient is diagnosed with osteoporosis, the PCP plays a key role in managing the condition. They can initiate treatment with medications such as bisphosphonates, calcium, and vitamin D supplements and refer the patient for physical therapy and exercise programs to help maintain bone health 73,74 . In addition to medical treatment with calcium and vitamin D, PCPs can also recommend a diet rich in calcium and vitamin D. Furthermore, PCPs can advise lifestyle modifications such as smoking cessation and limiting alcohol intake.…”
Section: Team Approachmentioning
confidence: 99%